Evaluation of person-centeredness in nursing homes after a palliative care intervention: pre- and post-test experimental design - Christina Bökberg; Lina Behm; Birgitta Wallerstedt; Gerd Ahlström (BMC Palliative Care, 2019)
Abstract Background The needs of care based on palliative principles are stressed for all people with progressive and/or life-limiting conditions, regardless of age and the place in which care is provided. Person-centred palliative care strives to make the whole person visible and prioritizes the satisfaction of spiritual, existential, social, and psychological needs to the same extent as physical needs. However, person-centred palliative care for older persons in nursing homes seems to be sparse, possibly because staff in nursing homes do not have sufficient knowledge, skills, and training in managing symptoms and other aspects of palliative care. Methods This study aimed to evaluate whether an educational intervention had any effect on the staff’s perception of providing person-centred palliative care for older persons in nursing homes. Methods: A knowledge-based palliative care intervention consisting of five 2-h seminars during a 6-month period was implemented at 20 nursing homes in Sweden. In total, 365 staff members were participated, 167 in the intervention group and 198 in the control group. Data were collected using two questionnaires, the Person-centred Care Assessment Tool (P-CAT) and the Person-Centred Climate Questionnaire (PCQ-S), answered before (baseline) and 3 months after (follow-up) the educational intervention was completed. Descriptive, comparative, and univariate logistical regression analyses were performed. Results Both the intervention group and the control group revealed high median scores in all subscales at baseline, except for the subscale amount of organizational and environmental support in the P-CAT. The staff’s high rating level of person-centred care before the intervention provides limited space for further improvements at follow-up. Conclusion This study shows that staff perceived that managers’ and the organization’s amount of support to them in their everyday work was the only area for improvement in order to maintain person-centred care. The experiences among staff are crucial knowledge in understanding how palliative care can be made person-centred in spite of often limited resources in nursing homes. The dose and intensity of education activities of the intervention model need to be tested in future research to develop the most effective implementation model. Trial registration NCT02708498. Date of registration 26 February 2016.